Linking Mathematics and Community: The Ethnomathematics of Bubo Fishing in the Coastal Town of Barbaza, Antique, Philippines - Tolentino, James (Journal of Interdisciplinary Perspectives, 2025)
In the Philippines, connecting pedagogy to local experiences, interests, and aspirations of the wider school community is an essential feature in the new educational curriculum. Traditionally, however, the relevance of cultural contexts has been inadequate in mathematics classrooms. The study of ethnomathematics offers insight into how and why mathematics remains integral to the various activities of an artistic community. Bridging the gap between mathematics and the real world may introduce learners to learn in a culturally responsive way. Thus, exploring various opportunities for interconnecting mathematics and culture is essential to enhance teaching and learning. This rapid ethnographic research aimed to investigate the ethnomathematical aspects of bubo fishing, one of the traditional fishing methods in the town of Barbaza, Antique. This study aimed to gather data on the diverse ethnomathematical practices, skills, and knowledge of the local fisherfolk. Five key informants were chosen through purposive sampling. The data for this study were collected through participant observation and ethnographic interviews. Data triangulation, member checking, and audit trail were used to establish the validity of the data. Spradley’s four-part ethnographic analysis revealed that ethnomathematics is embedded in the bubo fishing activities of the local fisherfolk. This study demonstrates that the local fishing community is rich in ethnomathematical knowledge, providing valuable mathematical information that may inspire and guide educators in developing and designing context-based curriculum content and teaching-learning materials. By making mathematics more relatable and demonstrating its practical value, educators can inspire a generation of learners who appreciate the power of mathematical concepts and their relevance in the real world. Further research is recommended to document the local mathematization of other cultural communities.